Development of Creative Mathematics Learning Model Based on Mathematical Disposition and Character Value - Jamiah, Yulis (Journal of Ecohumanism, 2025)
Mathematics, as one of the fundamental disciplines, has an important role in shaping the ability to think critically, logically, and systematically. This research aims to develop a creative mathematics learning model based on character values and examine the mathematical disposition of students in the Mathematics Education Study Program at FKIP Untan. This study used Borg & Gall's Developmental Research approach, which involves a cyclical process from conceptual model development to implementation and evaluation. The research participants used one class with a total of 30 students who were sampled in the study. The research procedure includes theoretical analysis of character values and mathematical disposition, exploration of student characteristics, identification of field problems, development and validation of learning models, and model implementation through real action research. The developed model focused on creating an effective, fun, and learning atmosphere centered on internalizing character values such as confidence, creativity, flexibility, and curiosity. The results showed that this learning model was effective in improving students' mathematical thinking ability, mathematical power, and mathematical disposition. This can be seen from the students' positive responses, where 53% responded very positively and 47% positively to the learning. In addition, the model validation showed excellent results, with an average score of 3.73 and 3.74 out of a maximum score of 4. In conclusion, the creative mathematics learning model based on character values is feasible to be applied in mathematics learning to support the development of students' thinking skills and attitudes optimally. Further research is recommended to further explore the development of character values that support the generation of active, creative, and responsible students.